The Impact of Integrating Multicultural Education and Islamic Values: Enhancing Tolerance and Social Skills in Elementary Schools - Ade Bagus Permana Putra; Yusi Putri Lailatul Musyarofah (Islamika Inside: Jurnal Keislaman dan Humaniora, 2025)
Multicultural education in elementary schools plays a crucial role in creating an inclusive learning environment that values diversity. This education introduces students to various cultures while fostering tolerance and enhancing their social and emotional skills. Multicultural programs involving interactive activities such as discussions, role-playing, and collaborative projects have proven effective in reducing prejudice and stereotypes, as well as increasing appreciation for differences. Students engaged in these programs not only show greater understanding and respect for diversity but also experience a decrease in bullying behaviour within the school environment. The integration of Islamic values such as tolerance, justice, and compassion into the multicultural curriculum strengthens inclusive attitudes and reduces prejudice, helping students develop character with strong ethics and morals. This Islam-based approach not only enriches students' learning experiences but also supports their character development and social skills, creating a more harmonious and cohesive learning environment while reinforcing positive attitudes among students. Thus, multicultural education that combines cultural and religious values holds great potential for building a more inclusive and harmonious society.